2017
DOI: 10.1262/jrd.2016-164
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized prairie vole-derived fibroblasts (VMF-K4DTs) can be transformed into pluripotent stem cells and provide a useful tool with which to determine optimal reprogramming conditions

Abstract: The cellular conditions required to establish induced pluripotent stem cells (iPSCs), such as the number of reprogramming factors and/or promoter selection, differ among species. The establishment of iPSCs derived from cells of previously unstudied species therefore requires the extensive optimization of programming conditions, including promoter selection and the optimal number of reprogramming factors, through a trial-and-error approach. While the four Yamanaka factors Oct3/4, Sox2, Klf4, and c-Myc are suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Our research group previously reported that combined expression of R24C mutant cyclin-dependent kinase 4 (CDK4), Cyclin D1, and telomere reverse transcriptase (TERT) allowed us to efficiently immortalize human- (Shiomi et al, 2011), cattle and pig- (Donai et al, 2014), prairie vole- (Katayama et al, 2016(Katayama et al, , 2017, monkey- (Kuroda et al, 2015a), midget buffalo- (Fukuda et al, 2016), and mega bat- (Tani et al, 2019), Tsushima wildcat-derived cells (Gouko et al, 2018). Furthermore, growth acceleration with mutant CDK4 and Cyclin D1 is conserved even in sea turtles, suggesting that the underlying cell cycle mechanism was well-conserved throughout animal evolution (Fukuda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group previously reported that combined expression of R24C mutant cyclin-dependent kinase 4 (CDK4), Cyclin D1, and telomere reverse transcriptase (TERT) allowed us to efficiently immortalize human- (Shiomi et al, 2011), cattle and pig- (Donai et al, 2014), prairie vole- (Katayama et al, 2016(Katayama et al, , 2017, monkey- (Kuroda et al, 2015a), midget buffalo- (Fukuda et al, 2016), and mega bat- (Tani et al, 2019), Tsushima wildcat-derived cells (Gouko et al, 2018). Furthermore, growth acceleration with mutant CDK4 and Cyclin D1 is conserved even in sea turtles, suggesting that the underlying cell cycle mechanism was well-conserved throughout animal evolution (Fukuda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…showed that immortalised human myogenic cells maintained their original nature as myogenic stem cells, with the intact chromosome condition 10 . We previously demonstrated the immortalisation of fibroblast cell lines derived from bovine, porcine 9 and non-human primate species 11 , midget buffalo 14 , prairie vole 12 , 13 , 32 , bovine colon epithelial cell 8 by transgene expression of human mutant CDK4, Cyclin D and TERT. The success of the immortalisation relies on the conserved homology of the cell cycle regulators, CDK4 and Cyclin D, over multiple species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our research group previously reported that expression of human-derived mutant Cyclin-dependent kinase 4 (CDK4), Cyclin D and Telomerase Reverse Transcriptase (TERT) efficiently immortalises cells of various mammalian species, including human, bovine 8 , swine 9 , 10 , monkey 11 , prairie vole 12 , 13 and midget buffalo 14 . We designated this recently developed method as K4DT, based on the identities of the introduced genes (mutant CD K4 , Cyclin D and T ERT).…”
Section: Introductionmentioning
confidence: 99%
“…This immortalization method using mutant CDK4, Cyclin D1, and TERT was termed "K4DT" in reference to the introduced genes. The chromosomal pattern of cells established using the K4DT method is retained, along with the nature of primary cells, possibly due to the intact function of p53 [13,[15][16][17]. We also recently demonstrated that our corneal epithelial cell line, established with the K4DT immortalization method, can be a useful tool to detect eye toxicity, and it can be used as a new resource for in vitro ocular toxicity testing [18].…”
Section: Introductionmentioning
confidence: 89%
“…Our research group has previously reported efficient immortalization in multiple species via co-expression of R24C mutant cyclin-dependent kinase 4 (CDK4 R24C ), Cyclin D1, and telomere reverse transcriptase (TERT) [8][9][10][11][12][13][14]. This immortalization method using mutant CDK4, Cyclin D1, and TERT was termed "K4DT" in reference to the introduced genes.…”
Section: Introductionmentioning
confidence: 99%